2021
DOI: 10.3138/cjpe.69703
|View full text |Cite
|
Sign up to set email alerts
|

UEval: Bringing Community-Based Experiential Learning to the Evaluation Classroom

Abstract: This practice note describes the unique features of, and lessons learned from UEval, an innovative one-week ‘evaluation institute’ at the Faculty of Extension, University of Alberta. This initiative responds to an identified community and university need to provide contextual and socially relevant evaluation-focused educational opportunities to learners across disciplines and sectors. UEval is a guided by principles of participatory and experiential learning, and brings together undergraduates, graduates and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Incorporating evaluator competencies was one of the recurrent recommendations throughout the literature, and it was identified that incorporating these competencies as student learning outcomes was the most effective way to align evaluation practices with industry needs and prepare students for professional practice (Gokiert et al, 2021; LaVelle & Galport, 2020; Poth & Searle, 2021). Of these professional competencies, the most important for practice were identified by Galport and Azzam (2017) as professional practice, systematic inquiry and interpersonal competence, which were also the competencies the study identified as needing the most training.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating evaluator competencies was one of the recurrent recommendations throughout the literature, and it was identified that incorporating these competencies as student learning outcomes was the most effective way to align evaluation practices with industry needs and prepare students for professional practice (Gokiert et al, 2021; LaVelle & Galport, 2020; Poth & Searle, 2021). Of these professional competencies, the most important for practice were identified by Galport and Azzam (2017) as professional practice, systematic inquiry and interpersonal competence, which were also the competencies the study identified as needing the most training.…”
Section: Discussionmentioning
confidence: 99%